Exploring Single-Atom Nanozymes Toward Environmental Pollutants: Monitoring and Control - Guojian Wu; Si Li; Linpin Luo; Yuechun Li; Wentao Zhang; Heng Wang; Sha Liu; Chenxing Du; Jianlong Wang; Jie Cheng; Yongning Wu; Yizhong Shen (Nano-Micro Letters)
Highlights Review of the state-of-the-art synthesis strategies for single-atom nanozymes. Analysis of the recent advances in single-atom nanozymes for monitoring and control of environmental pollutants. Challenges and perspectives of single-atom nanozymes in environmental pollutants monitoring and control.